2013
DOI: 10.9775/kvfd.2012.8461
|View full text |Cite
|
Sign up to set email alerts
|

Bir Ceylanda (Gazella gazella) Generalize Reaktif Amiloidoz Olgusu

Abstract: ÖzetBu raporda 1.5 yaşında, erkek bir dağ ceylanında saptanan generalize reaktif amiloidozis tanımlandı. Makroskobik incelemede karın boşluğundaki serozalarda hiperemi ve rumende ise kenarları kanamalı 7 cm çapında ülser belirlendi. Her iki böbreğin yüzeyinde 1-2 mm büyüklüğünde boz-beyaz renkte odaklar gözlendi. Mikroskobik incelemelerde böbreklerde glomerulus, tubulus ve akıtıcı kanal bazal membranları ve damar duvarlarında, dalakta foliküllerde, karaciğerde Disse aralığında ve ince barsaklarda lamina propri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Cases of generalized or localized amyloidosis have been reported previously in partridges (McMartin et al 1996, Kapakin et al 2010. It is known that the only type of amyloid observed in poultry is amyloid A, which is encountered in recurrent or chronic infections (McMartin et al 1996, Kapakin et al 2010, Özdemir et al 2013, Hauck et al 2019. In a study investigating the mortality of partridges with typhlohepatitis and amyloidosis, it was reported that a high rate of T. gallinarum sequence homology was obtained (Hauck et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cases of generalized or localized amyloidosis have been reported previously in partridges (McMartin et al 1996, Kapakin et al 2010. It is known that the only type of amyloid observed in poultry is amyloid A, which is encountered in recurrent or chronic infections (McMartin et al 1996, Kapakin et al 2010, Özdemir et al 2013, Hauck et al 2019. In a study investigating the mortality of partridges with typhlohepatitis and amyloidosis, it was reported that a high rate of T. gallinarum sequence homology was obtained (Hauck et al 2019).…”
Section: Discussionmentioning
confidence: 99%